A new "nuclear normalcy"?. (October 2019) - Schmid, Sonja D
This article focuses on a part of the "nuclear condition" that is often overlooked in philosophical discussions: that of materiality. Connecting the spheres of nuclear weapons (and associated security threats), and of nuclear power generation (and associated safety concerns), are the materials that bombs and electricity can be made of, and the machines that produce either enriched uranium or plutonium. We now have evidence of just how fragile the machines and devices were (and are) that sustained the nuclear age, but also how tenuous and artificial the boundary is that we assume between "peaceful" and "military" purposes. And yet, each new "nuclear deal" affirms this boundary, and the possibility of its existence. While the community of scholars and policymakers who prioritize nuclear security strive to label as many steps of the process as "special, " and therefore subject to inspection, accounting, and international control, multinational power companies and national nuclear industries promote "technical fixes" for lingering safety concerns, and advance the opposite strategy: to "normalize" many processes to the point of including severe accident response into the industry's business-as-usual. The article argues that different kinds of "nuclearities" have increasingly become accepted as "normal": on one hand, international diplomacy that foregrounds legal and regulatory strategies to nip potential nuclear weapons programs in the bud, and on the other, national nuclear power programs growing their fleets and attempting to expand their market reach. By accepting the divide between the "security community" and the "safety community" as the new "nuclear normalcy, " the shared nuclear materiality threatens to slip out of view, or at the very least, out of focus.